Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let binary operation $ \circ $ on set $X$ be function $\circ : X \times X \rightarrow X$.

Binary operation on set X is :

  • unitary if for some element $1 \in X$ and any $x \in X$ we've got $(1 \circ x) = x = (x \circ 1)$

  • alternate if for any $x,y \in X$ we've got $x \circ y = y \circ x$.

Show that:

1) $x \circ (y \circ x) = y \implies (x \circ y) \circ x = y$

2) Let $\circ$ and $\star$ be binary operation on $X$. $\circ$ and $\star$ are unitary and for any $a,b,c,d \in X$ we've got $(a \circ b) \star (c \circ d) = (a \star c) \circ (b \star d)$. Show that $\star$ and $\circ$ are alternate and identical.

Thanks for help.

share|improve this question
    
FYI, "alternate" is more commonly called "commutative" or "abelian". –  Chris Eagle Jun 30 '13 at 19:06
    
Thanks :D I used google translate :) –  JohnCina51 Jun 30 '13 at 19:28
1  
What have you tried? –  Vectk Jun 30 '13 at 19:33

3 Answers 3

Here’s an explicit, fully-defined example showing that (1) is false in general.

$$\begin{array}{c|cc} \circ&a&b\\ \hline a&b&b\\ b&a&b \end{array}$$

Then

$$a\circ(b\circ a)=a\circ a=b\;,$$

but

$$(a\circ b)\circ a=b\circ a=a\;.$$

share|improve this answer

Number 1 is false. Let $X = \{1, 2, 3, 4, 5\}$

We can have $1 \circ (2 \circ 1) = 2$ with $2 \circ 1 = 3$, but $(1 \circ 2) \circ 1 = 5$ with $1 \circ 2 = 5$.

share|improve this answer
1  
How do you know the values of the result of operating by $\circ$? –  triomphe Jun 30 '13 at 19:05
1  
@MLT The user didn't mention anything about the binary operation. I'm defining it however I want. –  user84510 Jun 30 '13 at 19:14
    
@MLT You cannot prove this implication without additional assumptions on $\circ$. I have defined a binary operation that doesn't satisfy it. –  user84510 Jun 30 '13 at 19:25
    
Well, you haven't defined it, but you started defining it. :) –  Thomas Andrews Jul 23 '13 at 20:48

2) Let $a=c=1$ then, $$b\star c=c \circ b \qquad(1)$$ Then you can use this identity (1) to change order as $$(b \star a) \star (d \star c) = (b \star d) \star (a \star c).$$ Then let $b=c=1$ so, $$ a \star d = d \star a,$$ which implies that $\star$ is alternative. You can prove for $\circ$ similarly. Now that $\star$ is alternative we can rewrite (1) as $$c\star b=c \circ b,$$which proves that $\star$ and $\circ$ are identical.

share|improve this answer
1  
Be careful - there might be different $1$ elements for $\star$ and $\circ$." –  Thomas Andrews Jul 23 '13 at 20:41
    
Which $1$ do you mean when you set $a=c=1$? –  Thomas Andrews Jul 23 '13 at 20:47

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.